ANALISIS STILISTIKA PADA CERPEN “KUTUKAN DAPUR” KARYA EKA KURNIAWAN - Lasenna Siallagan; Hodtua Lestari Rajagukguk3; Elsa Mayora; Kartika Bestari (FKIP, Universitas Palangka Raya, 2023)
This research was carried out based on the curiosity of researchers towards Stalistic Analysis in a short story by Eka Kurniawan entitled